Accidental Hypothermia Simulation - Deann Hoelscher; Raymond Ten Eyck (Association of American Medical Colleges, 2013)
Abstract This resource is an emergency medicine simulation designed to provide residents with a clinical experience that simulates diagnosis and treatment of hypothermia with septic joint in a patient presenting with altered mental status. Included are an assessment sheet and a debriefing sheet to be used after the case is completed to aid in learning. Although the simulation patient is a mannequin and not really alive, simulation participants should approach the simulation patient the same way and with the same sense of urgency that they would a real-life patient. This case was tested on four separate occasions with residents in their third year of training. The feedback was unanimous that this would be a good case for residents in their second year or early in their third year of training. We plan on incorporating this case into the second-year resident simulation curriculum.